Bone Health Should Be an Important Concern in the Care of Patients Affected by 21 Hydroxylase Deficiency. (21st September 2010) - Bachelot, Anne; Chakhtoura, Zeina; Samara-Boustani, Dinane; Dulon, Jérome; Touraine, Philippe; Polak, Michel
Abstract : Osteoporosis has been an understandable concern for children and adult patients with congenital adrenal hyperplasia (CAH) who may receive or have received supraphysiological doses of glucocorticoids. Some previous reports on bone mineral density (BMD) in adult CAH patients showed no significant differences in BMD between patients with CAH and controls, but others have found lower BMD in CAH patients. In reports documenting the BMD reduction, this outcome has been attributed to an accumulated effect of prolonged exposure to excess glucocorticoids during infancy and childhood. We recently conducted a trial to establish the role of the total cumulative glucocorticoid dose on BMD. We established for the first time that there was a negative relationship between total cumulative glucocorticoid dose and lumbar and femoral BMD. Women might benefit from the preserving effect of estrogens compared to men. BMI (Body Mass Index) also appeared to protect patients from bone loss. In light of this, physicians should bear in mind the potential consequences of glucocorticoids on bone and therefore adjust the treatment and improve clinical and biological surveillance from infancy. Furthermore, preventive measures against corticosteroid-induced osteoporosis should be discussed right from the beginning of glucocorticoid therapy.